The Information Content of FDI Announcements: Evidence from an Emerging Market - DING, David K. (Institutional Knowledge at Singapore Management University, 1997)
This study examines the stock return responses to the announcements of foreign direct investments (FDI) by Singaporean companies. A standard event study methodology is used to ascertain the abnormal returns around the announcement day (day 0). The study covers the period from 1989 to 1994 with a sample size of 70 events. The announcement effect is positive and significant around the announcement day. The average abnormal return is 0.4913 percent on day 0, and the two-day (days 0 and 1) cumulative abnormal return is 0.9642 percent. However, the abnormal return is unequally distributed across the sample firms. A cross-sectional analysis reveals that the two-day cumulative abnormal return of a firm is statistically significantly related to (1) the industry the FDI is in, and (2) whether the FDI is independent in nature or is in the form of a joint venture. It is, however, found to be unrelated to the country of investment. The evidence further shows that investors who trade on the information regarding a company's impending foreign investment can earn abnormal returns, net of transaction costs, by buying the stock before the event period and selling it five days after the announcement date.